Calcific coronary embolization associated with cardiac valve replacement. Necropsy x-ray study. Issue 8 (August 1976) - Steiner, I; Hlava, A; Procházka, J
Abstract : The hearts of 14 patients dying early after replacement of a calcified aortic or mitral valve were examined for the presence of calcific coronary emboli. The incidence of embolization as shown by x-ray film was 92-9 per cent. The number of emboli in individual cases ranged from 4 to 119. Replacement of an aortic valve was associated with a more severe embolization than replacement of a mitral valve. Th mechanisms of calcific embolization are discussed and preventive surgical measures suggested.